Seed Morphology and Germination Studies on Carpinus viminea for Conservation in North-Western Himalaya - SHIV PAUL; SS SAMANT (Seed Research, 2026)
Carpinus viminea (Himalayan Hornbeam) is one of the rare and multipurpose tree species of the Indian Himalayan Region. Over-exploitation for fuel, fodder and house building, habitat degradation and poor regeneration of species may lead to the extirpation of species. Therefore, seed morphology, seed viability and seed germination were investigated. Seeds were collected from Kanawar (2244m), Kandhi (1952m) and Khokhan (1472m) populations in Kullu district of Himachal Pradesh. They were dried for a week at room temperature and stored at 4º C in refrigerator. Tetrazolium test was used for the seed viability. The stored seeds were treated with gibberellic acid (GA3 15, 25 and 35µM), indole acetic acid (IAA 15, 25 and 35µM) and potassium nitrate (KNO3 130, 150 and 170mM). Maximum seed viability (80.0%, each) was recorded in Kanawar and Kandhi populations. 1000 seed weight increases with the increase in altitude. Maximum seed length (4.19±0.05mm), 1000 seeds weight (9.2gm), seed width (3.10±0.02mm) and seed thickness (1.92±0.02) were recorded in Kanawar population. Therefore, seeds collected from Kanawar population were selected for germination. In control condition, seed germination and Mean Germination Time (MGT) was poor. Treatments applied to the seeds improved germination % significantly (F = 14.793, p